Kinerja Keuangan Perusahaan Manufaktur Makanan dan Minuman pada Pandemi Covid-19 - Intan Putri Fandini (tesco publisher, 2023)
Covid-19 first appeared in Wuhan (China) at the end of 2019 and spread globally in early 2020. The government issued various policies to reduce positive cases such as lockdowns, PSBB (Large-Scale Social Restrictions), PPKM (Implementation of Restrictions on Community Activities). However, this policy actually makes Indonesia's economic activity difficult. As a result, there was a decline in economic growth, consumption, investment, and import-export trade. This research aims to examine developments and differences in financial performance before and during the COVID-19 pandemic in food and beverage sub-sector companies listed on the IDX. The Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Assets, and Economic Value Added measure financial performance. The research sample consisted of 20 companies with observations from 2018-2021. This type of research is quantitative research with data sourced from secondary data in the form of annual financial reports of food and beverage sub-sector companies downloaded via the web www.idx.co.id. The data analysis techniques used are descriptive statistics, classical assumption testing, and hypothesis testing. Based on the analysis carried out using Excel and SPSS 26, the results were obtained: (1) there was a decrease in CR, TATO, ROA, and EVA, while DER increased from before to the time of the Covid-19 pandemic, (2) there was no significant difference from CR, DER, TATO, ROA, and EVA between before and during the Covid-19 pandemic.